Feeding ecology of the leaf fish Monocirrhus polyacanthus (Perciformes: Polycentridae) in a terrafirme stream in the Brazilian Amazon - Catarino, Michel Fabiano (2010)
Monocirrhus polyacanthus (Polycentridae) is a remarkable leaf-mimicking fish that inhabits streams, lake and river margins along the Amazon basin. Despite its obvious predatory habits and being frequently present in the international aquarium trade, little is known about its diet under natural conditions. We examined 35 specimens of leaf fish (28.5-82.0 mm SL), of which 19 had food the stomach. Thirty-three preys were found in the stomach contents, 19 of which were measured (2.0-33.0 mm total length). Up to five preys were found in the stomach contents of a single leaf fish specimen. The diet of the leaf fish was constituted by fish (63.15% FO, n = 12) and invertebrates (36.3% FO, n = 4); fish and invertebrate preys occurred together in three stomachs (15.8% FO). Of the 33 prey found in the stomachs, 21 were fish and 12 invertebrates. Among the consumed prey fishes, Characiformes and Perciformes represented 76.1% and 14.2% respectively. Characidae was the most commonly recorded prey family, followed by Lebiasinidae. Invertebrates were represented by shrimps (Decapoda) and insects (Coleoptera, Hymenoptera, Ephemeroptera and Odonata). There was a positive relation between the size of the leaf fish specimens and of its consumed preys. The combination of leaf fish's visually effective body camouflage and the reduced activity of the characids at crepuscular hours probably allow the capture of such fast moving preys. The coiled position of the fishes found in the stomach of M. polyacanthus possibly allowed the accommodation of more than one prey simultaneously, which seems to be important for predators that consume proportionally large preys that are captured only occasionally. © 2010 Sociedade Brasileira de Ictiologia.